Changing panorama in risk factors of cerebral palsy - Dogruoz Karatekin Bilinc; Icagasioglu Afitap (Vojnosanitetski Pregled)
Background/Aim. The etiology of cerebral palsy (CP) is multifactorial and not yet fully understood. The aim of this study was to determine the changes in CP etiological factors over the past 30 years. Methods. A retrospective study analyzed a database of 296 individuals with CP. Risk factors (RFs) were divided into preconception, antenatal, intrapartum, and neonatal. Patients on the register were divided into three cohorts: those born before 2000, the ones born between 2000 and 2010, and those born after 2010. The changes in CP RFs were investigated at ten-year intervals. Results. The five RFs with the highest total frequency were low birth weight (46.62%), prematurity (44.25%), advanced maternal age – over 35 years (37.16%), emergency cesarean section (33.78%), and birth asphyxia (25.33%). The consanguineous marriage rate was 22.29%. Conclusion. Low birth weight and prematurity rates, which are the most frequently identified RFs, are gradually increasing. The rate of birth asphyxia has decreased in the last ten years. The rate of advanced maternal age is increasing, and consanguineous marriage is still an important RF in Turkey.